Pelatihan Pengembangan Multimedia Pembelajaran Interaktif : Suatu Analisis Kebutuhan - Harina Fitriyani; Dwi Astuti (Ethos: Jurnal Penelitian dan Pengabdian kepada Masyarakat, 2022)
Abstract. The development of interactive multimedia learning is a skill that teachers need to master in supporting the smooth teaching and learning activities, especially during a pandemic like the current one where learning is carried out online. However, teacher skills are still not evenly distributed in developing interactive learning media to support interesting online learning for students. Therefore, it is necessary to carry out interactive learning multimedia development training to train teachers to develop interactive learning media and learning videos to support the implementation of online learning. Before the training is carried out, it is necessary to analyze the needs for the performance of the training on interactive multimedia learning. Thus, this study aimed to analyze the need for the performance of training on the development of interactive multimedia learning. The survey method was chosen with 15 teachers as respondents in one of the Muhammadiyah Junior High Schools in Bantul, Yogyakarta. Data analysis used simple descriptive statistics. The questionnaire results given via Google Form show that the respondents' knowledge of several useful applications for developing their interactive multimedia learning is generally still in the low category. Therefore, it is necessary to create interactive learning multimedia for teachers to help teachers carry out teaching and learning activities in a pandemic situation and equip teachers with teaching skills in the post-pandemic era.